Labor Productivity Study in Construction Projects Viewed from Influence Factors - Rusdi U. Latief; N. M. Anditiaman; I. R. Rahim; R. Arifuddin; M. Tumpu (Salehan Institute of Higher Education, 2023)
Productivity is one of the fundamental factors affecting competitiveness in the construction industry. Construction and productivity are two things that are interrelated. This study aims to identify the factors and model relationship these factors that affect labor productivity using the Structural Equation Modelling (SEM) in road construction projects in Indonesia as seen from each side area I, II, and III, respectively. The results obtained the factors that influence labor productivity in road construction projects in Indonesia, namely field conditions, time, financial factors, and internal labor. The study's findings indicate that internal labor is one of the elements influencing labor productivity in Indonesian construction projects, particularly road maintenance work. Labor productivity research in Indonesia is conducted by comparing planned and realized labor productivity calculations, which are conducted by collecting project data and making firsthand observations of work in the field. Labor productivity is measured using characteristics other than the variables used in the research, as well as a larger population and sample coverage. The findings of this study can be utilized as input for government agencies in determining the ability of specialists to carry out work in the field connected to the preservation of non-structural flood handling roads on Indonesian territory. Doi: 10.28991/CEJ-2023-09-03-07 Full Text: PDF